Effects of tumor necrosis factor antagonists in patients with primary sclerosing cholangitis - Hedin, Charlotte; Sado, Gina; Ndegwa, Nelson; Lytvyak, Ellina; Mason, Andrew; Montano-Loza, Aldo; Gerussi, Alessio; Saffioti, Francesca; Thorburn, Douglas; Nilsson, Emma; Larsson, Geir; Moum, Bjørn A.; et al. (Clinical gastroenterology and hepatology, 2020)
Background & Aims - Few patients with primary sclerosing cholangitis (PSC) and inflammatory bowel diseases (IBDs) are exposed to tumor necrosis factor (TNF) antagonists because of the often mild symptoms of IBD. We assessed the effects of anti-TNF agents on liver function in patients with PSC and IBD, and their efficacy in treatment of IBD. - Methods - We performed a retrospective analysis of 141 patients with PSC and IBD receiving treatment with anti-TNF agents (infliximab or adalimumab) at 20 sites (mostly tertiary-care centers) in Europe and North America. We collected data on the serum level of alkaline phosphatase (ALP). IBD response was defined as either endoscopic response or, if no endoscopic data were available, clinical response, as determined by the treating clinician or measurements of fecal calprotectin. Remission was defined more stringently as endoscopic mucosal healing. We used linear regression analysis to identify factors associated significantly with level of ALP during anti-TNF therapy. - Results - Anti-TNF treatment produced a response of IBD in 48% of patients and remission of IBD in 23%. There was no difference in PSC symptom frequency before or after drug exposure. The most common reasons for anti-TNF discontinuation were primary nonresponse of IBD (17%) and side effects (18%). At 3 months, infliximab-treated patients had a median reduction in serum level of ALP of 4% (interquartile range, reduction of 25% to increase of 19%) compared with a median 15% reduction in ALP in adalimumab-treated patients (interquartile range, reduction of 29% to reduction of 4%; P = .035). Factors associated with lower ALP were normal ALP at baseline (P < .01), treatment with adalimumab (P = .090), and treatment in Europe (P = .083). - Conclusions - In a retrospective analysis of 141 patients with PSC and IBD, anti-TNF agents were moderately effective and were not associated with exacerbation of PSC symptoms or specific side effects. Prospective studies are needed to investigate the association between use of adalimumab and reduced serum levels of ALP further.
Gesehen am 29.09.2020